REPRESENTASI PEMASARAN MELALUI MAJALAH MINI MENGGUNAKAN MEDIA SOSIAL INSTAGRAM - Muhamad Yusup; Nurlaila Suci Rahayu Rais; Yunita Kartika Sari (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2018)
Writing this article made to modern society who want program market products easier, efficient, effective and practical, in search for a information and obtained a products, the community generally maximize a means of communication equipped the internet, with the progress communications device equipped internet facilities, the community spoiled by forms application supported under the internet, through technological progress media instagram so provided facilities in the form of display visualizations interesting, easy to remember and easy to use. The method in use very simple, using just electronic devices such as pc computer, smartphone, and tablet ordinary use a day in day by modern society, because the device easy access it with visualization display features a feature provided. Through the instagram, held in public offering find the kind of product products, get reference style fashion, kinds of food, locations to visited tourism, forms of information actual and factual can be found.